Murder at Sunrise Lake [large type] - Feehan, Christine (Thorndike Press, a part of Gale, a Cengage Company, 2021)
It starts in her dreams. Hideous flashes from a nightmare only she can stop. Images of a murderer stalking the ones she cares about most. Stella Harrison thought she got away from the traumas of her past. Running the Sunrise Lake resort high in the Sierra Nevada mountains has brought her peace, even though she doesn't truly share her quiet life with anyone. Not even Sam, the hired handyman that notices everything and always seems to know exactly what she needs. Stella doesn't know anything about Sam's past but somehow over the last two years his slow, steady presence has slipped past her defences. Still, she knows she can't tell him about her recent premonitions. So far there's been no murder. No body. No way to prove what's about to happen without destroying the life she's built for herself. But a killer is out there. And Stella knows that this time she'll do whatever it takes to stop him.